2008
DOI: 10.1182/blood-2008-02-138073
|View full text |Cite
|
Sign up to set email alerts
|

Activation of natural regulatory T cells by IgG Fc–derived peptide “Tregitopes”

Abstract: We have identified at least 2 highly promiscuous major histocompatibility complex class II T-cell epitopes in the Fc fragment of IgG that are capable of specifically activating CD4 ؉ CD25 Hi FoxP3 ؉ natural regulatory T cells (nT Regs IntroductionInduction of specific tolerance to self-or to foreign antigens is the goal of therapy for autoimmunity, transplant rejection, and allergy; unresponsiveness is also desirable in the context of therapy with potentially immunogenic autologous proteins (such as factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
346
2
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 357 publications
(363 citation statements)
references
References 36 publications
13
346
2
2
Order By: Relevance
“…We cannot exclude the possibility that the IL-33-dependent T reg -cell activation is mainly mediated indirectly via dendritic cells, as previously described by Matta and coworkers (32). However, our data do not support a direct interaction of IVIG with any T-cell subset, as has been proposed (22), nor could we observe any evidence in support of IVIG providing "Tregitopes" (41)(42)(43)(44).…”
Section: Discussioncontrasting
confidence: 67%
“…We cannot exclude the possibility that the IL-33-dependent T reg -cell activation is mainly mediated indirectly via dendritic cells, as previously described by Matta and coworkers (32). However, our data do not support a direct interaction of IVIG with any T-cell subset, as has been proposed (22), nor could we observe any evidence in support of IVIG providing "Tregitopes" (41)(42)(43)(44).…”
Section: Discussioncontrasting
confidence: 67%
“…"Tregitopes" are one potential explanation for the tolerogenicity of Fc fusion proteins as described in 2008 [70]. Tregitopes are highly conserved, tolerogenic peptides, discovered during epitope mapping and deimmunization programs with human protein (especially IgG) therapeutics.…”
Section: Regulatory T Cell Epitopes In Igg Framework Regions: Tregitopesmentioning
confidence: 99%
“…S7). The potential to generate immune-stimulatory epitopes is another advantage of recombinant Id vaccines over native Ig Id vaccines, in addition to avoiding the regulatory T-cell epitopes found on Ig constant regions (38). Ding et al reported that B cells targeted by an anti-CD19-Ag conjugate could prime CD4 + T cells (39).…”
Section: Discussionmentioning
confidence: 99%